Molecular marker assisted gene stacking for biotic and abiotic stress resistance genes in an elite rice cultivar - Das, Gitishree; Rao, G. J. N. (Frontiers in Plant Science, 2015)
Severe yield loss due to various biotic stresses like bacterial blight (BB), gall midge (insect) and Blast (disease) and abiotic stresses like submergence and salinity is a serious constraint to the rice productivity throughout the world. The most effective and reliable method of management of the stresses is the enhancement of host resistance, through an economical and environmentally friendly approach. Through the application of marker assisted selection (MAS) technique, the present study reports a successful pyramidization of genes/QTLs to confer resistance/tolerance to blast (Pi2, Pi9), gall Midge (Gm1, Gm4), submergence (Sub1) and salinity (Saltol) in a released rice variety CRMAS2621-7-1 as Improved Lalat which had already incorporated with three BB resistance genes xa5, xa13 and Xa21 to supplement the Xa4 gene present in Improved Lalat. The molecular analysis revealed clear polymorphism between the donor and recipient parents for all the markers that are tagged to the target traits. The conventional backcross breeding approach was followed till BC3F1 generation and starting from BC1F1 onwards, marker assisted selection was employed at each step to monitor the transfer of the target alleles with molecular markers. The different BC3F1s having the target genes/QTLs were inter crossed to generate hybrids with all ten stress resistance/tolerance